2010
DOI: 10.2175/193864710798159282
|View full text |Cite
|
Sign up to set email alerts
|

Microconstituents: What to Expect in Your Permit

Abstract: Microconstituents are beginning to make their way into newspaper headlines and discharge permits in the United States. Removal of microconstituents often requires tertiary treatment, and utilities are interested to know what permit limits they might expect in the future as they plan for capital improvements. EPA is currently focusing on developing methods for determining the endocrine disrupting impact of a given compound. EPA has developed some criteria for endocrine disrupting compounds (EDCs), but the state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Some U.S. states have already established provisional health advisories for some PFCs for drinking water (e.g. Minnesota, New Jersey) and residential soils.A review of U.S. EPA and state regulations found that although the U.S. EPA has developed some recommended limits for certain EDCs in fresh water, few states have developed these into standards or discharge permits(Reeves and Littlehat, 2012). Several states are in the process developing standards for diazinon, PCBs, Water Environment Research, Volume 85, Number 10-Copyright © 2013 Water Environment Federation nonylphenol, atrazine, and tributyltin.…”
mentioning
confidence: 99%
“…Some U.S. states have already established provisional health advisories for some PFCs for drinking water (e.g. Minnesota, New Jersey) and residential soils.A review of U.S. EPA and state regulations found that although the U.S. EPA has developed some recommended limits for certain EDCs in fresh water, few states have developed these into standards or discharge permits(Reeves and Littlehat, 2012). Several states are in the process developing standards for diazinon, PCBs, Water Environment Research, Volume 85, Number 10-Copyright © 2013 Water Environment Federation nonylphenol, atrazine, and tributyltin.…”
mentioning
confidence: 99%